Conditionally immortalised leukaemia initiating cells co-expressing Hoxa9/Meis1 demonstrate microenvironmental adaptation properties ex vivo while maintaining myelomonocytic memory - Maike Stahlhut (Nature Portfolio, 2021)
Abstract Regulation of haematopoietic stem cell fate through conditional gene expression could improve understanding of healthy haematopoietic and leukaemia initiating cell (LIC) biology. We established conditionally immortalised myeloid progenitor cell lines co-expressing constitutive Hoxa9.EGFP and inducible Meis1.dTomato (H9M-ciMP) to study growth behaviour, immunophenotype and morphology under different cytokine/microenvironmental conditions ex vivo upon doxycycline (DOX) induction or removal. The vector design and drug-dependent selection approach identified new retroviral insertion (RVI) sites that potentially collaborate with Meis1/Hoxa9 and define H9M-ciMP fate. For most cell lines, myelomonocytic conditions supported reversible H9M-ciMP differentiation into neutrophils and macrophages with DOX-dependent modulation of Hoxa9/Meis1 and CD11b/Gr-1 expression. Here, up-regulation of Meis1/Hoxa9 promoted reconstitution of exponential expansion of immature H9M-ciMPs after DOX reapplication. Stem cell maintaining conditions supported selective H9M-ciMP exponential growth. H9M-ciMPs that had Ninj2 RVI and were cultured under myelomonocytic or stem cell maintaining conditions revealed the development of DOX-dependent acute myeloid leukaemia in a murine transplantation model. Transcriptional dysregulation of Ninj2 and distal genes surrounding RVI (Rad52, Kdm5a) was detected. All studied H9M-ciMPs demonstrated adaptation to T-lymphoid microenvironmental conditions while maintaining immature myelomonocytic features. Thus, the established system is relevant to leukaemia and stem cell biology.